The Adventures of David Simple and Volume the Last - Fielding, Sarah, 1710-1768 (Book collections on Project MUSE., 1998)
A two-volume reprint--restoring original text-- of an 18th century novel on the pitfalls of friendship. The hero, David Simple, is a man repeatedly deceived by people to whom he became attached. In the first volume he is cheated of his fortune, but regains it, in the second he loses it for good.